B-13 GROWTH AND CHARACTERIZATION OF CO-DOPED FLUORINE AND ANTIMONY IN TIN OXIDE THIN FILMS OBTAINED BY ULTRASONIC SPRAY PYROLYSIS(Session: Coatings/Thin Films) - Thitinai Gaewdang; Ngamnit Wongcharoen; Auppatham Nakaruk; Nattaporn Promros (My University, 2006)
SnO_2: F,Sb thin films were prepared by an ultrasonic spray pyrolysis method. The as-deposited films were annealed at 500℃ in three different conditions: in nitrogen, in air and in vacuum respectively. The XRD analysis showed that the undoped SnO_2 films grown in (200) preferred orientation whereas the fluorine and antimony doped films grown in (110) plane. Sheet resistance and resistivity values decrease to minimum value when films were annealed in N_2. Optical transmittance percentage in the IR region decreases in the annealed films. For the films were annealed in N_2, the lowest percentage of transmittance values in IR region was also elucidated.
Keywords: Tin oxide; Fluorine; ZnO doping and properties